2018
DOI: 10.1007/s00167-018-5194-x
|View full text |Cite
|
Sign up to set email alerts
|

High tibial osteotomy increases patellofemoral pressure if adverted proximal, while open-wedge HTO with distal biplanar osteotomy discharges the patellofemoral joint: different open-wedge high tibial osteotomies compared to an extra-articular unloading device

Abstract: Purpose Valgus high tibial osteotomy (HTO) and a recently introduced extra‐articular absorber have been shown to efficiently unload the medial compartment of the knee. However, only little is known about the influence of these treatment modalities on biomechanics of the patellofemoral joint. The purpose of this study was to investigate and compare the impact of different HTO techniques and implantation of an extra‐articular absorber on patellofemoral contact forces. Methods Fourteen fresh frozen cadaveric knee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 31 publications
2
25
0
5
Order By: Relevance
“…Previous studies noted that valgus alignment could lead to a higher incidence of pathology in the patellofemoral joint. 16,37 The postoperatively realigned mechanical axis usually falls on the preoperatively planned target point in most patients who undergo MOWHTO. However, under-or overcorrection of the mechanical axis occurs in some patients for various reasons, even after meticulous planning.…”
mentioning
confidence: 99%
“…Previous studies noted that valgus alignment could lead to a higher incidence of pathology in the patellofemoral joint. 16,37 The postoperatively realigned mechanical axis usually falls on the preoperatively planned target point in most patients who undergo MOWHTO. However, under-or overcorrection of the mechanical axis occurs in some patients for various reasons, even after meticulous planning.…”
mentioning
confidence: 99%
“…The most important findings of this study were the following three: Firstly, preoperative elevated BTU values in the patellar region correlated significantly with a worse clinical outcome. It was previously shown that MOWHTO leads to an increase of the contact pressure in the patellofemoral joint (PFJ) [15,19,20,25,37,39]. Kim et al [19] suggested that the increased loading of the PFJ may be the cause of postoperative pain and be associated with the development and progression of OA in the PFJ.…”
Section: Discussionmentioning
confidence: 99%
“…[1,19] Dolayısıyla bu osteotomi tekniği PF kondromalazisi olan hastalarda da tercih edilebilir. [20]…”
Section: Bağ Lezyonu Olan Dizlerde Yapılan Proksimal Tibial Osteotomi (Pto)unclassified